Pengaruh Manajemen Pemasaran, Kreativitas, Inovasi, dan Lokasi terhadap Loyalitas Konsumen (Studi Kasus Usaha Mie Aigo di Kamal) - Rukmaningrum, Nikalawasta Ananda; Arisinta, Octaviana (Universitas Batanghari, 2024)
Opening a restaurant business or the trend called a restaurant is currently more popular with entrepreneurs. Moreover, recently types of food such as noodles have been admired by many people, especially noodle lovers. When starting a business, you must pay attention not only to preparing materials and finances, but being ready to take risks is an important thing to overcome existing problems. That way, entrepreneurs have to work harder to gain and maintain consumer loyalty. This research was conducted to determine the influence of marketing management, creativity, innovation and location on consumer loyalty (Case Study of the Aigo Noodle Business in Kamal). The aim of this research is to determine the influence of marketing management, creativity, innovation and location on consumer loyalty (case study of the Aigo noodle business in Kamal) partially and simultaneously. The type of research used was quantitative with a Likert scale and 30 respondents. The sampling Technique in the research used Convenience Sampling. The research results showed that the marketing management variable (X1) had a significant influence on consumer loyalty. This is proven by a value of 0.001 < 0.05 and Tcount of 3.654 > 2.060. So Ho is rejected, and Ha is accepted. The creativity variable (X2) has a negative but significant influence on consumer loyalty. This is proven by a significance value of 0.000 <0.05 and a T value of -6.356 <2.060. So Hoe was rejected and Ha was accepted. The innovation variable (X3) has a negative but significant influence on consumer loyalty. This is proven by a significance value of 0.034<0.05 and a Tcount value of -2.244<2.060. So Hoe was rejected and Ha was accepted. The location variable (X4) has a significant influence on consumer loyalty. This is proven by a significance value of 0.000 <0.05 and a T value of 6.015> 2.060. So Hoe was rejected and Ha was accepted. Testing F, it can be concluded that there is a simultaneous influence between marketing management variables (X1), creativity (X2), innovation (X3), location (X4) on consumer loyalty variables (Y). This is proven by a significant value of 0.000 <0.05 and Fcount of 54.996 > 2.76. This means that there is a simultaneous influence between marketing management variables (X1), creativity (X2), innovation (X3), location (X4) and consumer loyalty variables (Y).